2021
DOI: 10.18632/aging.203247
|View full text |Cite
|
Sign up to set email alerts
|

Aging-dependent loss of GAP junction proteins Cx46 and Cx50 in the fiber cells of human and mouse lenses accounts for the diminished coupling conductance

Abstract: The homeostasis of the ocular lens is maintained by a microcirculation system propagated through gap junction channels. It is well established that the intercellular communications of the lens become deteriorative during aging. However, the molecular basis for this change in human lenses has not been well defined. Here, we present evidence to show that over 90% of Cx46 and Cx50 are lost in the fiber cells of normal human lenses aged 50 and above. From transparent to cataractous lenses, while Cx43 was upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…In comparison, Cx50 is initially synthesized in the epithelium and remains at high levels in differentiating fiber and mature fiber cells [ 13 , 14 , 15 ]. Interestingly, a recent study by Gong et al [ 16 ] reported that human and mouse lenses have different distribution patterns of connexin proteins. For example, in contrast to the mouse lens, where Cx46 is primarily expressed in the fiber cells [ 17 , 18 ], both Cx46 and Cx50 in the human lens are expressed in the epithelial cells of transparent and cataractous lenses.…”
Section: Connexins and Intercellular Communication In The Lensmentioning
confidence: 99%
See 3 more Smart Citations
“…In comparison, Cx50 is initially synthesized in the epithelium and remains at high levels in differentiating fiber and mature fiber cells [ 13 , 14 , 15 ]. Interestingly, a recent study by Gong et al [ 16 ] reported that human and mouse lenses have different distribution patterns of connexin proteins. For example, in contrast to the mouse lens, where Cx46 is primarily expressed in the fiber cells [ 17 , 18 ], both Cx46 and Cx50 in the human lens are expressed in the epithelial cells of transparent and cataractous lenses.…”
Section: Connexins and Intercellular Communication In The Lensmentioning
confidence: 99%
“…For example, in contrast to the mouse lens, where Cx46 is primarily expressed in the fiber cells [ 17 , 18 ], both Cx46 and Cx50 in the human lens are expressed in the epithelial cells of transparent and cataractous lenses. Gong et al [ 16 ] further reported that the ratio between Cx43 and Cx46/Cx50 in humans is 9:1, which is higher than in mice (5:1), indicating a different expression pattern of connexin isoforms. Although transcripts for a fourth connexin, Cx23, have been detected in the zebrafish embryo and mouse lens, there is no report for its expression in the human lens [ 19 , 20 ].…”
Section: Connexins and Intercellular Communication In The Lensmentioning
confidence: 99%
See 2 more Smart Citations
“…Age and oxidative stress in the lens are usually coincident and lead to changes in the lens proteome, including connexin channel density and regulation ( Gao et al, 2013 ; Gong et al, 2021 ; Quan et al, 2021 ). The lens is protected from oxidative damage by antioxidants, such as GSH, and chaperone proteins to prevent protein aggregation and dissolution from oxidative stress ( Giblin, 2000 ; Lim et al, 2020 ).…”
Section: Aging and Oxidative Stress Impact The Channels Underlying The Lens Circulationmentioning
confidence: 99%